Aprendendo a aprender pensando sobre como pensar: o desenvolvimento de competência em informação sobre o suporte da metacognição - Melo, Ana Virgínia Chaves de (2016)
Considering that the Metacognitive processes would be the most appropriate basis for the development of competence in information, aimed to analyze the influence of Metacognitive processes in the development of competence in information, in relation to the production process of academic texts in teachers and students graduates of undergraduate degree in library science from Federal University from Paraíba (UFPB). To this end, a theoretical foundation on the topics: information literacy weaving the Process of Information Search of Kuhlthau (2010); studies on information search of Ellis, Cox and Hall (1993) and the concept of self-efficacy of Learning Sociocognitive Theory of Bandura (1996). Cognitive psychology clarified the processes of memory, language and cognition. The Metacognition brought the Metamemory and Metacomprehension theories on reading and writing, showing the connections between the three areas described. We used the method of Grounded Theory, life history and the critical incident as ways of listening to the experiences that make explicit the cognitive and Metacognitive solutions used by participants of the research to the problems of information, being conducted semi-structured interviews, about their search, and reading and writing practices with ten teachers and nine students on the last semester from undergraduate degree in library science from UFPB. The interviews were transcribed and the responses were analysed through continued comparative analysis from the Grounded Theory methodology. As a result, we identified the cognitive and Metacognitive processes and strategies in relation to cognitive challenges of the subjects and examined the influence of Metacognition on the development of competence in information. As theoretical product were perceived central axes of cognition and Metacognition in relation to the development of competence in information. Points, then (1) a metacognitivo mechanism of awakening the need of information, from the interaction of constructs like interest and Metacognitive State of alert; (2) a theoretical understanding of informational flows at the Academy based on perception of four interconnected networks as a means of access to knowledge in the academic space: the network of information systems, and authoring, and content and intellectual production. (3) reading processes take as a basis the transit and the ability to interact with these networks to feed his own internal semantic network of the student and the teacher, who, (4) upon becoming authors, become providers of products to the same networks where sought information, generating a stream of continuous academic production. These understandings indicate the practical importance may take at the Academy and in the area of Information Science developing competence in information and have the need to expand the spaces of knowledge and discussion about the development of information competence, their interrelations with Metacognition and the possibilities included in the understanding of the flow of scientific information networks and their transactions as theoretical instrument for understanding the development of competence in information. It was also perceived the need for discussion that make learning about competence in information and Metacognition to enlarge the possibilities of developing competence in information and, as a result of textual production academic area.